Trend and prevalence of transfusion transmitted infections among blood donors in rural teaching institute, south India - MS Leena; Shafee Mohd (Association of Clinical Pathologists of Nepal, 2012)
Background: The magnitude of transfusion transmitted infections (TTI) varies from country to country depending on TTI’s load in that particular population. The aim of the study was to study the trend and prevalence of sero-markers among blood donors in one of the tertiary health center in south India. Materials and Methods: A retrospective cross-sectional study was performed from 2004 to 2010 in a blood bank of teaching hospital in South India. All blood donors who presented to blood bank during the study period were included. Data regarding demography and serological tests were collected on predesigned proforma. Results: There were a total of 6939 blood donors during study period. Out of these, 94(1.35%) were positive for sero-markers for TTIs. The number of blood donors as well as sero-positivity increased from year 2004 to 2010. Conclusions: Trend and sero-prevalence of TTIs increased over period of time. Sero-positivity for TTIs decreased from year 2004 to 2010. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6022 JPN 2012; 2(3): 203-206